Epidemiología y antropología histórica. Para una mejor comprensión de los estragos producidos por las enfermedades en el siglo XVI - Perera, Miguel Ángel (Revista Española de Antropología Americana, 2003)
The main subject of this paper is to expose the necessary integration of epidemiological and ecological considerations in the ethnohistorical study about demographic consequences of contact between European and natives groups in the New World. Developed models, of regional or local validity, connecting both perspectives, will permit to surpass the analytical poverty frequently observed in traditional anthropologic studies.